Synthetic Cannabis Overdose and Withdrawal in a Young Adult: A Case Report, Commentary on Regulation, and Review of the Literature - John Samaan; Gerardo F. Ferrer; Boye Akinyemi; Patricia Junquera; Juan Oms; Rhaisa Dumenigo (Case Reports in Psychiatry)
Introduction. Marijuana has been used for its psychotropic effects including enhanced relaxation and perceptual alterations. However, the use of synthetic marijuana (SM) leads to more frequent and drastic side effects than the typical use of regular marijuana, owing to the fact that SM has a shorter duration and an earlier peak of action. Despite all the potential adverse health effects associated with SM use, current health policies on SM are very limited. It is believed that the popularity of SM has increased, due to its easy accessibility in the US and lack of detection in typical urine drug screens for THC. Case Report. One case presented is of a young adult patient, with histories of recurrent synthetic cannabis and recreational cannabis use, who had developed drastic physiological and psychiatric symptoms, including the development of acute-onset psychosis. Conclusion/Discussion. This case, as many others nationwide, exemplifies the impact of synthetic cannabinoid use and abuse in adolescents. Side effects and adverse health consequences of synthetic cannabinoid use warrant stricter regulations and policies in order to decrease psychiatric hospital admissions and associated healthcare costs.